"Target‐Lesion" SYNTAX Score (tSS) Determines Radiation Dose in Percutaneous Coronary Intervention. (April 2015) - HEE, LEIA; THOMAS, LIZA; ULLAH, INAAM; JUERGENS, CRAIG P.; LO, SIDNEY; HOPKINS, ANDREW; FRENCH, JOHN K.; MUSSAP, CHRISTIAN J.
<x xml:space="preserve">Abstract</x> Objectives To investigate the correlation between "target‐lesion" SYNTAX score (tSS) and radiation dose (RD) and examine the predictive value of tSS and other variables on RD from percutaneous coronary intervention (PCI). Background The complexity of PCI influences procedural RD. The novel tSS was utilized to quantify targeted‐PCI complexity. Methods We studied 420 consecutive patients who had PCI in our hospital. Two investigators independently measured tSS using the SYNTAX scoring algorithm. Patients were divided into three BMI (kg/m 2 ) subgroups: <25 (normal), 25–30 (overweight), and >30 (obese); and tSS tertiles: <5.5 (simple), 5.5–9 (moderate), and >9 (complex). Results Obese patients were significantly younger and likely to have diabetes mellitus (DM). tSS positively correlated with RD for both genders, with median RD significantly higher in males (P < 0.0001). tSS correlated with RD in all three BMI subgroups (all P < 0.0001). Multivariate linear regression showed RD can be predicted by the formula: RD = −898 + 18 tSS + 49 BMI + 142 DM + 207 male. Conclusions We report that tSS is a quantitative index of "target‐lesion" PCI complexity, which is easy to measure with good reproducibility. tSS significantly and independently correlates with RD, although the strength of the association is less than for other predictors of RD (gender, diabetes, and BMI). tSS may be used to determine the RD from PCI and enhance patient risk‐stratification when formulating a PCI strategy.